The influence of perceived benefits on young Malaysian Facebook users’ homestay reservation intention / Phang Ing @ Grace, Zaiton Bt. Osman and Tania Imboh Ak Stephen Arin - Ing, Grace Phang; Osman, Zaiton; Stephen Arin, Tania Imboh (Universiti Teknologi MARA Cawangan Sarawak, 2017)
Portrayed as a rural hospitality product with unique Malaysian appeal, consumers’ intention to reserve a homestay could be very different from other lodging options. Unfortunately, empirical studies on homestay are insufficient, particularly in the Malaysian context. This paper aimed to examine how the Malaysian young adult’s intention to make a homestay reservation via social media platform such as Facebook, is influenced by perceived benefits. Utilizing structural equation modelling, the findings supported the influences of perceived functional, hedonic, social and monetary benefits on homestay reservation intention. Interestingly, psychological benefit was found to have a significant but negative relationship with reservation intention. This could be attributed to the unique characteristics of homestay which require active participation from both the customers and the homestay hosts. Compared to similarity, belonging and affiliation, young consumers preferred uniqueness and differences in the hosts’ cultures and lifestyles. The findings suggested the Facebook to be an effective tool for homestay operators. The promotional campaigns stress that the point of differences could be more effective and attractive to the young consumers.